Given: f1=f2=1 and for n∈N, fn+2=fn+1+fn.
Prove that f2+f4+⋯+f2n=f2n+1−1.
Would you start with setting f2+f4+⋯+f2n=an?
Then for the base case let a1=1 LHS=1 and RHS=2−1=1 so base case holds.
Then the inductive hypothesis: Assume f2+f4+⋯+f2n=f2n+1−1
NTS: f2+f4+⋯+f2n+f2n+2=f2n+3−1
Inductive step: By inductive hypothesis f2+f4+⋯+f2n=f2n+1−1
So f2n+1−1+f2n+1=f2n+2−1. As was to be shown.
Is this correct or did I need to show more algebra in my inductive step ?
Answer
Hint. The inductive step is rather
f2+f4+⋯+f2n+f2n+2=f2n+3−1,
then using the inductive hypothesis, we have to prove that
f2n+1−1+f2n+2=f2n+3−1.
Can you take it from here?
No comments:
Post a Comment